Factors associated with relief from acute pain among patients admitted in medical ward of Mbarara Regional Referral Hospital, south western Uganda: A cross-sectional study - Silas Ojuka; Robert Tamukong; Tadele Mekuriya Yadesa (PLoS ONE, 2025)
Acute pain is an understudied subject among patients admitted in medical wards, especially in sub-Saharan Africa. Given that it is one of the commonest causes of hospital admissions, it is necessary to diagnose and adequately treat it in time. Unrelieved acute pain may have negative consequences such as; reduced quality of life, prolonged hospital stays and increased cost of treatment. The purpose of this study was to assess relief of acute pain and factors associated with it in medical ward of Mbarara Regional Referral Hospital, South-Western Uganda. Severity of pain was determined using the Brief Pain Inventory. Adequate drug therapy for acute pain was assessed using the Pain Management Index. Relief from acute pain was considered a change in pain grade from severe to mild or moderate to mild or mild to no pain. This was done by comparing baseline pain grade at enrollment (day one) and follow up pain grade on day two. Multivariate logistic regression was performed to identify associated factors that had statistical significance. Out of 280 patients with acute pain, analgesic drug therapy was adequate for 32 (11.43%) participants while relief from acute pain was achieved among 95 (34%). Multivariate logistic regression showed female gender to be significantly associated with relief from acute pain (adjusted Odds Ratio=1.86; 1.11-3.10 at 95% C.I; p value=0.018). Prevalence of adequacy of analgesic drug therapy for acute pain among patients admitted in medical ward of Mbarara Regional Referral Hospital was low. Proportion of patients with relief from acute pain was also low. Female patients were more likely to experience relief from acute pain compared to their male counterparts.